2010
DOI: 10.1037/a0020325
|View full text |Cite
|
Sign up to set email alerts
|

Does emotion processing require attention? The effects of fear conditioning and perceptual load.

Abstract: This study examined the impact of perceptual load on the processing of unattended threat-relevant faces. Participants performed a central letter-classification task while ignoring irrelevant face distractors, which appeared above or below the central task. The face distractors were graded for affective salience by means of aversive fear conditioning, with a conditioned angry face (CS+), an unconditioned angry face (CS−), and a neutral control face. The letter-classification task was presented under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
76
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 47 publications
13
76
1
Order By: Relevance
“…This is in line with previous studies already showing that emotion processing is reduced under circumstances where attentional resources are limited (Pessoa, Padmala, & Morland, 2005;Yates, Ashwin, & Fox, 2010). When attentional demands are high and attentional resources are fully exhausted to some stimuli, attention is not allocated to emotional stimuli and emotion processing is not observed.…”
Section: Running Head: Influence Of Working Memorysupporting
confidence: 78%
See 1 more Smart Citation
“…This is in line with previous studies already showing that emotion processing is reduced under circumstances where attentional resources are limited (Pessoa, Padmala, & Morland, 2005;Yates, Ashwin, & Fox, 2010). When attentional demands are high and attentional resources are fully exhausted to some stimuli, attention is not allocated to emotional stimuli and emotion processing is not observed.…”
Section: Running Head: Influence Of Working Memorysupporting
confidence: 78%
“…In previous studies on top-down effects on emotional processing, attentional manipulation was a focus of interest (Pessoa et al, 2005;Yates et al, 2010). They investigated whether emotional stimuli attracted attention when participants were required to other nonemotional stimuli or features.…”
Section: Running Head: Influence Of Working Memorymentioning
confidence: 99%
“…A dynamic shift in the control of emotional distraction may well account for some discrepancies that have appeared in the literature regarding the ability of emotional images to capture attention, where some studies find that irrelevant emotional images that occur outside the focus of attention can disrupt processing (Fox, Dutton, Yates, Georgiou, & Mouchlianitis, 2015;Junhong et al, 2013;Yates, Ashwin, & Fox, 2010), but others show they do not (Lichtenstein-Vidne et al, 2012;Okon-Singer et al, 2007;Vromen et al, 2015). A systematic manipulation of proportion conflict may furthermore shed light on the modulation of other emotional effects such as those revealed with emotional Stroop, visual search, or spatial cueing paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Because attention is considered to be resource limited, one explanation may be that the load imposed in the attention task was high. The likelihood of attention capture has been shown to be greater under low load conditions, when residual capacity was available, than under high load conditions (14,41,42). We titrated the difficulty of the target color change so the monkeys' performance was between 70% and 90% correct, creating a high attentional load.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that capture only occurs in low perceptual load conditions (14,15). Functional MRI (fMRI) has shown that the amygdala response to affective stimuli is modulated by task demands (16,17).…”
mentioning
confidence: 99%